Desenvolvimento de metaheurísticas para o problema da árvore geradora mínima generalizado - Cristo, Fernando de (2008)
The generalized minimum spanning tree problem is present in several situations of the real world, such as in the context of the telecommunications, transports and grouping of data, where a net of necessary clusters to be connected using a node of each cluster. In that work it is presented the project and the implementation of an algorithm of tabu search with path relinking and iterated local search for the generalized minimum spanning tree problem and your variant with at least one vertex by group. In the computational tests 271 instances of TSPLIB were used generated through the grouping methods Center Clustering and Grid Clustering, and more 20 instances for the extension of the problem with at least one vertex by group. The results demonstrate the efficiency of the algorithm proposed in the obtaining of satisfactory solutions for the two problems.